Análisis de CRM para el seguimiento de clientes del gimnasio Águila Gym de la ciudad de Babahoyo. - Figueroa Barrozo, Edison Jordin (2022)
This case study was carried out in the Águila gym in the City of Babahoyo, whose main objective is to analyze the CRM for the follow-up of clients, for the development the methodology was obtained was descriptive since the needs of this gym were described. The research design was also quantitative, that is, a survey of seven questions previously elaborated was applied to 218 people to know the perception of the clients. The research method was inductive - deductive. In this work, we proceeded to compare three software to choose the one that best suits the needs of the gym and in this case it was CLUPIK, which is the one that fulfilled all the characteristics such as keeping customers informed, easy to use, among others. This work adjusts to the lines of research the research line of the career is an information and communication system entrepreneurship and innovation in conjunction with networks and intelligent technologies of software and hardware aligned to the subline.